Generation of OFDM signal with envelop pulse-width modulation (EPWM) transmitter employing 2nd-order delta-sigma modulator - Kawazoe, Koji (Animo Repository, 2008)
OFDM achieves high spectral efficiency in wireless communication systems. However, it is difficult ti achieve high power efficiency because of its large PAPR. Envelope Pulse-Width Modulation (EPWM) transmitters have been proposed to obtain high power efficiency for the amplification of OFDM signals. This paper proposes an EPWM transmitter which employs the 2nd order Δ-∑ modulator with a null-response frequency. Expression for quantization noise power is theoretically derived to estimate in-band and adjacent channel quantization noise power. The power spectral density (PSD) of the IEEE 802.11a OFDM signal generated with the transmitter is calculated changing the null-response frequency. The adjacent channel leakage power ratio (ACLR) of the OFDM output signal is calculated from the PSD. It is shown that the null-response frequency of 20 MHz give the minimum ACLR for the transmitter.